Localization of porcine seminal plasma (PSP) proteins in the boar reproductive tract and spermatozoa - Postlerová, Pavla; Jonáková, Věra (Journal of reproductive immunology, 2008)
Spermadhesins are proteins containing a characteristic CUB domain, originally isolated from seminal plasma and ejaculated spermatozoa in domestic animals. Boar spermadhesins are multifunctional proteins exhibiting ligand-binding abilities with various endogenous ligands present in the male and female reproductive tracts and may play a role in the reproduction process. Porcine spermadhesins (AQN, AWN, PSP protein families) are secreted mainly by the seminal vesicles, but their mRNAs have been found also in the cauda epididymis and prostate. Unlike AQN and AWN spermadhesins, localization of porcine seminal plasma (PSP) proteins in the boar reproductive tract has not been completely resolved. This work has focused on PSP protein expression and localization in the boar reproductive organs and on spermatozoa. Using specific rabbit polyclonal antibodies (anti-PSP I and anti-PSP II), PSP I and PSP II proteins were immunodetected in tissue extracts and in secretory tissues of cauda epididymis, prostate, seminal vesicles and Cowper's glands on the blots and by an indirect immunofluorescence technique, respectively. Moreover, the ability of PSP proteins to bind to epididymal spermatozoa indicated their presence on cauda epididymal and ejaculated spermatozoa. Porcine seminal plasma proteins bind to the sperm surface at ejaculation and may modulate several aspects of sperm activity during reproduction. PSP proteins are produced not only by seminal vesicles and prostate, but also by epididymis. However, their prospective role in sperm epididymal maturation is not clear. Further characterization of seminal plasma protein forms expressed in the individual reproductive organs will help to understand their subsequent role in the reproduction process.
Keywords: sperma; Reproduction; spermie; rozmnožování; regulace genové exprese; Female; mužské pohlavní orgány; financování organizované; Financing, Organized; zvířata; Genitalia, Male; Swine; Seminal Plasma Proteins; ženské pohlaví; Gene Expression Regulation; Male; Semen; proteiny semenné plazmy; Spermatozoa; Animals; mužské pohlaví; prasata